PROTEKSI BULLYING ANAK DI DUNIA CYBER PADA KOMISI PERLINDUNGAN ANAK DAERAH KOTA TASIKMALAYA - Ai Ilah Warnilah; Recha Abriana Anggraini; Deddy Supriadi; Mumun Surahman (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The development of internet technology has caused many crimes in the field of information technology or commonly called cybercrime or computer-related crime which are increasingly prevalent in Indonesia. One of crimes in cyberspace is Cyberbullying, this is a form of intimidation by one or more people to corner, other people through the cyber world. Cyberbullying can be defined as the use of internet technology to harm others intentionally and repeatedly. This intimidation is not arbitrary as a result, not infrequently death is the end of cyberbullying. Cyberbullying can also be interpreted as a form of intimidation carried out to harass its victims through technological devices. The partner in activity is the Regional Child Protection Commission (KPAD) of the City of Tasikmalaya which is an institution that also plays an important role in crime prevention, especially for minors. KPAD is an institution that is a party in protecting children as victims of crime and children who become perpetrators of crimes, KPAD in this case becomes a companion for children who want to get protection. To tackle crimes against children, an important role is needed from various groups, one of which is the family, therefore the academic community of BSI Tasikmalaya University held a Community Service (PPM) program with partners to disseminate bullying protection in the cyber world.